Effect of ionic liquid on the spontaneous combustion characteristics of noncaking pulverized coal - Li MA; Cheng-mao HE; Ze WEI; Gao-ming WEI; Yang WANG (工程科学学报, 2022)
To study the oxidation behavior induced by the spontaneous combustion of accumulated pulverized coal during its storage and transportation within an air leakage circumstance during increased oxidation and temperature and to reveal the mechanism of [BMIM][BF4] ionic liquid inhibiting oxidation and flame retardant characteristics of pulverized coal, this paper used a high-efficiency inhibitor [BMIM][BF4] ionic liquid to inhibit the noncaking coal pulverized coal of the Hongliu coal mine (HL), measuring the critical parameters (critical spontaneous combustion temperature, Tm, and ignition delay time, ti) of pulverized coal spontaneous combustion treated using [BMIM][BF4] at 5%, 10%, and 15% mass fraction. This work also analyzed the influence of [BMIM][BF4] on the heating and self-heating of the pulverized coal. Macroscopic resistance characteristics of [BMIM][BF4] to the pulverized coal were tested under the same high-temperature circumstance (all pulverized coals were ignited). Furthermore, an Fourier transform infrared experiment was used to characterize the microscopic resistance characteristics of the pulverized coal by [BMIM][BF4] to verify the variation of the critical parameters during pulverized coal spontaneous combustion. Results show that [BMIM][BF4] can efficiently inhibit the self-heating reaction of the pulverized coal, increase the Tm and ti values of the pulverized coal, and reduce the risk of pulverized coal spontaneous combustion. Moreover, a higher [BMIM][BF4] mass fraction results in a greater critical parameter of pulverized coal spontaneous combustion. Among them, the Tm of the coal powder treated by [BMIM][BF4] at a 15% mass fraction is 156 ℃, which is +26 ℃ longer than the original pulverized coal redundancy, and the ti is 80 min, which is 32 min later than the original pulverized coal ignition. Under a similar experimental temperature, Ta (Ta>Tm), the center point temperature, oxygen consumption rate, and CO production of pulverized coal treated by [BMIM][BF4] are all lower than those of the original pulverized coal, and the inhibition effect is enhanced with the increase in the mass fraction of [BMIM][BF4]. Meanwhile, the inhibited effect of [BMIM][BF4] is reflected in the strong electronegative fluorine atoms forming strong hydrogen bonds with the hydroxyl hydrogen atoms in coal, dissolving and destroying the hydroxyl groups in the coal and blocking the coal oxygen chain reaction.